Aircraft Repair and Withdrawal Costs Generated by Bird Collision with the Windshield - Aleksandra Nešić; Olja Čokorilo; Sanja Steiner (Promet - Traffic&Transportation, 2017)
According to available data released by the European Aviation Safety Agency (EASA) in the period from 1990 to 2007, more than 94,743 collisions with birds occurred on the territory of US, UK and Canada. In some parts of the world bird population is significantly growing. Also, the number of aircraft operations has increased in recent decades, and more importantly, their increase is expected in the future as well. In these conditions, the number of aircraft collisions with birds is expected to grow. Bird strikes are affecting safety and also generate additional costs in air traffic. This paper will show what type of bird strike costs exist with focus on repair and withdrawal of bird strike costs. Repair and withdrawal costs due to bird strike are specific because they could vary from insignificant amount up to millions of dollars and because of its unpredictability.